High prevalence of Erysipelothrix rhusiopathiae infection among abattoir workers in Kamuli District, Eastern Uganda - Musewa, A.; Roesel, Kristina; Nakanjako, D.; Kawoya, I.; Ssenyonga, R.; Nangendo, J.; Sam, A.; Erume, J.; Grace, Delia (2021)
Introduction: Erysipelothrix (E.) rhusiopathiae is a ubiquitous gram-positive bacterium, which causes erysipelas in swine, mammals, birds and erysipeloid in humans. A previous study conducted in Kamuli district, identified serotypes 1 and 2 in pigs thus a follow up study in humans aimed at establishing prevalence and factors associated with E. rhusiopathiae infection. Methods: We conducted a cross-sectional community-based epidemiological study using quantitative methods of data collection. The study enrolled 302 raw pork handlers (butchers, abattoir workers and cooks) in Kamuli district, Eastern Uganda. Erysipelothrix rhusiopathiae infection among the handlers was determined by collecting whole blood for culture. Bacteria were isolated and infection confirmed using biochemical tests and gram staining. In addition, a semi-structured questionnaire was administered to establish the risk factors of E. rhusiopathiae infection. Results: The overall prevalence of E. rhusiopathiae infection was 9.9 % (95% CI: 7.4-13). Being a raw pork handler and self-reported alcohol consumption increased the risk of acquiring the infection. Among butchers, the prevalence was 15% (95% CI: 5.9 - 25), abattoir workers 37% (95% CI: 21 - 52) and cooks 3.4% (95% CI: 1.0 - 5.9). Working in the abattoir and butchery made infection 26 times (OR = 26; 95% CI: 5.3 - 129) and 8 times (OR = 8.4; 95% CI: 1.8 - 39) more likely, respectively. Alcohol consumption was associated with E. rhusiopathiae infection (OR = 4.0; 95% CI: 1.1 - 15). Conclusion: E. rhusiopathiae infections exist in Kamuli district, Eastern Uganda affecting all categories of raw pork handlers. We recommend that the isolates be serotyped to identify the circulating serotypes and inform the appropriate control measures for the disease in humans.